Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and Their Nursing Care Providers - Muray, Mwali (Université d'Ottawa / University of Ottawa, 2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system.
Keywords: Francophonie; Linguistic Minorities; Nursing; Phenomenology; Qualitative Research